"I hate reading" overcoming shame in the reading classroom - Stygles, Justin M. (Corwin literacy)
"What would you do if you could answer the question, "Why do kids stop reading during the elementary years?" Kelly Gallagher brought this to our attention in his seminal text, Readicide. What if we could find the answer...? --Not by looking at cognitive abilities, but affect - the child's physical response, emotions, and perceptions, rather than means we have traditionally, e.g. reading comprehension. --With compassion: Through a long-term investment with readers, and by using relationships, or the interpersonal bridge, to rectify self-perception, and building competence and mastery so students can become truly independent, lifelong readers because reading matters to them! --By questioning our practices: what if the answer to why kids stop reading didn't come in test scores, but merely by looking into their eyes and listening to their story? I found myself asking these questions about seven years ago after life forced me into a deep self-reflection. When I began studying books like Shame: the Power of Caring, I saw more than myself on the pages, I saw my maturing readers. My students, subjected to accepted reading pedagogy, manifested behaviors in the same ways I was reading off the pages. I continued to read, drawing links between shame research and professional development literature about reading instruction. The connections were alarming. Following years of self-reflection and adaptations to my practices, I developed my own theories, many which are presented in this text"--Provided by publisher.